2019
DOI: 10.1109/lra.2019.2927954
|View full text |Cite
|
Sign up to set email alerts
|

GCNv2: Efficient Correspondence Prediction for Real-Time SLAM

Abstract: In this paper, we present a deep learning-based network, GCNv2, for generation of keypoints and descriptors. GCNv2 is built on our previous method, GCN, a network trained for 3D projective geometry. GCNv2 is designed with a binary descriptor vector as the ORB feature so that it can easily replace ORB in systems such as ORB-SLAM2. GCNv2 significantly improves the computational efficiency over GCN that was only able to run on desktop hardware. We show how a modified version of ORB-SLAM2 using GCNv2 features runs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 45 publications
(81 reference statements)
1
83
0
Order By: Relevance
“…Based on depth estimated by DEM, our SLAM achieves greater improvement in accuracy on the TUM dataset than others such as SLAM [10]- [12], [17], [18]. Additionally, our SLAM is low-cost as compared with RGBD camera-based SLAM [19], [20]. The results demonstrate that the DEM and DEM-based SLAM are effective.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on depth estimated by DEM, our SLAM achieves greater improvement in accuracy on the TUM dataset than others such as SLAM [10]- [12], [17], [18]. Additionally, our SLAM is low-cost as compared with RGBD camera-based SLAM [19], [20]. The results demonstrate that the DEM and DEM-based SLAM are effective.…”
Section: Introductionmentioning
confidence: 84%
“…Existing visual SLAM often relies on data from stereo cameras, monocular cameras [10], [11], [17], [18], [39], or RGBD cameras [12], [19], [20]. In research [10]- [12], [20], [39], the SLAM systems all employ deep learning techniques to extract features. Specifically, in approaches [12], [20], keypoints and descriptors are learned by CNN and RNN (recurrent neural network) for SLAM.…”
Section: Related Workmentioning
confidence: 99%
“…pure rotation) haven't been carefully handled; 2) More indepth and detailed research on the convergent properties of the inverse depth of the map point is needed; 3) Our approach adopts the classic ORB features of image in the whole SLAM framework. With the development of deep learning for feature extraction, such as the MagicPoint [27] and GCN features [28], in future we will try to replace the ORB features with the deep-learning features to further improve the robust of our system.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Global consistency is then achieved by means of loop closure detection and global pose graph optimization. Another variation of ORB-SLAM2 can be found in [121], where ORB features were replaced by learnt point features, referred to as GCNv2. It was demonstrated that the proposed approach has comparable performance to ORB-SLAM2 in most scenarios, but performs slightly better in case of fast rotations.…”
Section: Resilience To Feature Detection/association Failurementioning
confidence: 99%